Investigation on Process Stability and Part Positioning Influence on the Relative Density of Designed Materials via Laser‐Based Powder Bed Fusion of Metals on a Multi‐Laser Machine. Issue 1 (29th July 2021) - Albert, Johannes; Hermann, Oliver; Purschke, Simon; Rule, David; Fleck, Claudia
Abstract : Component production via laser‐based powder bed fusion of metals (PBF‐LB/M) is becoming reality for multiple applications. Especially for sophisticated parts, as in case of gas turbines, assurance of repeatable properties involves control of process and machine parameters. PBF‐LB/M is used to build configurable open‐porous structures—designed materials (DMs)—out of the high temperature superalloy Haynes 282 with relative densities from 35 % to 65 % . The objective is investigating positioning influence and process stability based on their relative densities in discrete scan fields and build jobs. As DMs made from Haynes 282 are not yet scientifically investigated, first the process boundaries are identified. The used PBF‐LB/M machine—EOS M 400‐4—works with four lasers in four quadrants—a quadrant benchmarking is carried out. The experiment is repeated in a second build job. Scatter is identified in quadrant and build job benchmarking. A further aspect under investigation is positioning within laser quadrants. However, keeping laser and parameter combinations constant, sample locations are assessed. A relative density dependency on the laser deflection angle—as a positional measure—is observed. The results of positioning influence and scatter are used to formulate a tolerance equation for relative densities of DMs. Abstract : Laser‐based powder bed fusion of metals (PBF‐LB/M) is used to build configurable open‐porous structures—designed materials (DMs)—out of a high temperature superalloy. First the process boundaries are identified. The objective is investigating the positioning influence and process stability. The results of positioning influence and scatter are used to formulate a tolerance equation for relative densities of DMs.